Teaching music to the educable mentally retarded children - Canisguin, Gloria G. (College of Education, University of the Philippines Diliman, 1975)
The primary purpose of the study is to present suggested musical activities which will help facilitate the learning development of educable mentally retarded children in the intermediate level. The core of the study consists of ten sample lessons showing the suggested musical activities which are categorized into the six areas of teaching music namely, singing, listening, moving, playing, creating, and music reading. The materials in the study have been adapted to suit the particular characteristics of the educable mentally retarded children in the intermediate level as well as the availability of materials and resources needed in the teaching of music in the public school set-up.